Analysis of terms used for the diagnosis and classification of amyotrophic lateral sclerosis and motor neuron disease. Issue 7 (16th November 2016) - Rutter-Locher, Zoe; Turner, Martin R.; Leigh, P. Nigel; Al-Chalabi, Ammar
Abstract: There is no test for amyotrophic lateral sclerosis (ALS) and so attempts have been made to produce standardized diagnostic criteria based on clinical and electrophysiological findings, e.g. El Escorial. However, the phenotypic classification of the subtypes of ALS is also based on clinical features leading to conflation of diagnosis and phenotype. We used a five-question online survey with ALS specialists to explore the range of descriptors and how they are used. Of 101 specialists approached, 72 completed the survey. The most frequently used labels were 'ALS', 'PLS' and 'familial'. Labels other than the El Escorial categories were mainly used as clinical descriptors (83%). Approximately 50% of respondents recorded that the El Escorial criteria had no useful role in patient discussion or in the diagnostic process. Only 31% of respondents rated their current classification system above the median for being logical. A more rational system explicitly distinguishing diagnostic and phenotypic criteria is essential.